Using Padlet to Enable Online Collaborative Mediation and Scaffolding in a Statistics Course - Henrik Skaug Sætra (MDPI AG, 2021)
Students often perceive statistics as a difficult subject, and it is frequently named as one of the primary causes of high dropout rates in economics educations in Norway. In order to support the learning process in statistics courses, and in order to make the courses more flexible, the author experimented with the use of Padlet in two different student groups taking an introductory course in statistics for economists. The purpose was to overcome the difficulty of engendering social engagement and activity and fostering effective mediation, scaffolding and collaborative learning in large student groups scheduled for traditional lectures in large auditoriums. The author's experiences and the students' evaluations of the model is presented here, along with the theoretical justification of the use of Padlet and the context in which it was tested. The results show that computer-supported collaborative learning can be an effective supplement or alternative to traditional study groups for those that either prefer this or cannot take part in regular study groups. The students used Padlet actively, and a majority of the students reported that it was a significant or highly significant factor in their learning process.